Rural Tourism Development: Assessing the Role of Accessibility in Enhancing Sumber Bulu Village's Appeal - Zairil, Zairil (Akademi Komunitas MAPINDO, 2024)
Accessibility is widely recognized as a crucial factor in the development of rural tourism, directly impacting visitor numbers and local economic growth. While much of the literature emphasizes the importance of transportation infrastructure and information dissemination in attracting tourists, gaps remain in understanding how these factors play out in specific rural contexts. In particular, there is limited research on how accessibility influences rural tourism development in remote, culturally rich areas like Sumber Bulu Village, Solo. Addressing this gap, the present study investigates the role of accessibility in enhancing the tourism potential of Sumber Bulu Village. Using a qualitative case study approach, the research incorporates in-depth interviews with local stakeholders and direct observations to assess how transportation infrastructure influences tourist arrivals. The literature review underscores the pivotal role of accessibility in making rural destinations attractive to tourists. The findings reveal that although Sumber Bulu Village possesses abundant cultural and natural resources, suboptimal transportation infrastructure is a significant barrier to its development as a prominent tourism destination. Improvements in road conditions and enhanced promotional efforts are necessary to unlock the village's full potential. In conclusion, this study highlights the need for strategic investments in accessibility to foster tourism growth in rural areas. The local government is encouraged to improve transportation links and increase marketing initiatives to promote the village's unique offerings. Limitations of the study include a lack of comprehensive data on tourist demographics and existing infrastructure, suggesting avenues for future research to further validate these findings.